The woman elementary school principal perception of her feminine and community roles - Paredes, Teresita S. 1936-
This study presents a description of the concepts of the feminine and community roles of female public elementary school principals in Manila City, Quezon City, Pasay City, Caloocan City, Makati, Malabon, Navotas, Mandaluyong, Parañaque, San Juan, and Las Piñas. Their feminine roles are measured through the Inventory of Feminine Values and their community roles through the Community Role Defining Instrument and the Semantic Differential Style of Behavior Measurement